Idaarah Manaahij Ta'liim Al Lughah Al 'Arabiyyah di Al Madrasah Al 'Aliyah Lappariaja Bone - Alam, Syamsu; Rosyidi, Abdul Wahab (IAIN Bone, 2020)
The purpose of this paper is to present curriculum management in Arabic learning. The obstacles that arise as well as the steps that must be done in overcoming the obstacles in the implementation of Arabic language learning curriculum management in MAN Lappariaja Bone District. This research is field research with a descriptive qualitative research type. The results showed that the application of curriculum management in Arabic learning in MAN Lappariaja Bone Regency had been running well in a variety of cross-curriculum which was carried out through management functions although there were still some obstacles encountered in its application, the obstacles in its application were the application of management functions. by each individual within the scope of the madrasa organization has not been distributed optimally, lack of integration between the old curriculum with the new curriculum, and the steps that must be taken are strengthening management functions, building sustainable synergy between the old curriculum and the new curriculum. , and curriculum adaptation to the reality of education in MAN Lappariaja Bone Regency without reducing the essence and substance of the curriculum.